(untitled) (Journal of Information Technologies in Education (ITE), 2012)
The article deals with the peculiarities of the use of information and communication technologies (ICT) in the process of the quality education management in private gynasiums. The social importance and the novelty of private education as well as the role of the education quality management and in the same time the lack of practical realization of the effective mechanisms caused the search of the effective technologies of the quality management. The structure of information education environment was proposed into the article. The main goal is to give opportunity to be effective and operative in the process of decision making. The positive influence on the education process was underlined.